2021
DOI: 10.3390/rs13040545
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Variations of Plasmaspheric Total Electron Content from Topside GPS Observations on LEO Satellites

Abstract: The plasmasphere is located above the ionosphere with low-energy plasma, which is an important component of the solar-terrestrial space environment. As the link between the ionosphere and the magnetosphere, the plasmasphere plays an important role in the coupling process. Therefore, it is of great significance to study the electron content variation of the plasmasphere for the solar-terrestrial space environment. Nowadays, the topside global positioning system (GPS) observations on Low Earth Orbit (LEO) satell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Previous studies have shown that the change of the PTEC is closely related to solar radio flux at 10.7 cm (Jin et al., 2021; Zhang et al., 2016). PTEC can be calculated by the following formula (Foelsche and Kirchengast, 2002; Jin et al., 2021; Zhang et al., 2016): normalPnormalTnormalEnormalC=normalpnormalonormaldnormalTnormalEnormalC×normalf(ε) $\mathrm{P}\mathrm{T}\mathrm{E}\mathrm{C}=\mathrm{p}\mathrm{o}\mathrm{d}\mathrm{T}\mathrm{E}\mathrm{C}\times \mathrm{f}(\varepsilon )$ normalf(ε)=sin0.25emε+Rppt/Rorb2(cosε)21+Rnormalpnormalpnormalt/Rnormalonormalrnormalb $\mathrm{f}(\varepsilon )=\frac{\mathrm{sin}\,\varepsilon +\sqrt{{\left({R}_{\mathrm{p}\mathrm{p}\mathrm{t}}/{R}_{\mathrm{o}\mathrm{r}\mathrm{b}}\right)}^{2}-{(\cos \,\varepsilon )}^{2}}}{1+{R}_{\mathrm{p}\mathrm{p}\mathrm{t}}/{R}_{\mathrm{o}\mathrm{r}\mathrm{b}}}$ Rnormalpnormalpnormalt=RE+Hnormalpnormalpnormalt ${R}_{\mathrm{p}\mathrm{p}\mathrm{t}}={R}_{E}+{H}_{\mathrm{p}\mathrm{p}\mathrm{t}}$ Rnormalonormalrnormalb=RE+Hnormalonormalrnormalb ${R}_{\mathrm{o}\mathrm{r}\mathrm{b}}={R}_{E}+{H}_{\mathrm{o}\mathrm{r}\mathrm{b}}$ where normalf(ε) $\mathrm{f}(\varepsilon )$ is the conversion coefficient, podTEC is precise orbit determination (POD) antenna TEC me...…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have shown that the change of the PTEC is closely related to solar radio flux at 10.7 cm (Jin et al., 2021; Zhang et al., 2016). PTEC can be calculated by the following formula (Foelsche and Kirchengast, 2002; Jin et al., 2021; Zhang et al., 2016): normalPnormalTnormalEnormalC=normalpnormalonormaldnormalTnormalEnormalC×normalf(ε) $\mathrm{P}\mathrm{T}\mathrm{E}\mathrm{C}=\mathrm{p}\mathrm{o}\mathrm{d}\mathrm{T}\mathrm{E}\mathrm{C}\times \mathrm{f}(\varepsilon )$ normalf(ε)=sin0.25emε+Rppt/Rorb2(cosε)21+Rnormalpnormalpnormalt/Rnormalonormalrnormalb $\mathrm{f}(\varepsilon )=\frac{\mathrm{sin}\,\varepsilon +\sqrt{{\left({R}_{\mathrm{p}\mathrm{p}\mathrm{t}}/{R}_{\mathrm{o}\mathrm{r}\mathrm{b}}\right)}^{2}-{(\cos \,\varepsilon )}^{2}}}{1+{R}_{\mathrm{p}\mathrm{p}\mathrm{t}}/{R}_{\mathrm{o}\mathrm{r}\mathrm{b}}}$ Rnormalpnormalpnormalt=RE+Hnormalpnormalpnormalt ${R}_{\mathrm{p}\mathrm{p}\mathrm{t}}={R}_{E}+{H}_{\mathrm{p}\mathrm{p}\mathrm{t}}$ Rnormalonormalrnormalb=RE+Hnormalonormalrnormalb ${R}_{\mathrm{o}\mathrm{r}\mathrm{b}}={R}_{E}+{H}_{\mathrm{o}\mathrm{r}\mathrm{b}}$ where normalf(ε) $\mathrm{f}(\varepsilon )$ is the conversion coefficient, podTEC is precise orbit determination (POD) antenna TEC me...…”
Section: Discussionmentioning
confidence: 94%
“…Science question 2: Can we ignore the contribution of geomagnetic activity to PTEC? Most of LEO-based TEC studies have focused on the investigation of the topside ionospheric responses to geomagnetic storms (Astafyeva, 2009;Astafyeva et al, 2015;Kuai et al, 2017;Lei et al, 2014Lei et al, , 2015Lei et al, , 2016Mannucci et al, 2005;Zhong et al, 2016a) and other climatology characteristics of the topside ionosphere and plasmasphere (Jin et al, 2021;Noja et al, 2013;Pedatella and Larson, 2010;Yizengaw et al, 2008;Zhang et al, 2016;Zhong et al, 2017). There have been very limited long-term studies on the impact of different geomagnetic conditions on the PTEC.…”
Section: Discussionmentioning
confidence: 99%
“…CMEs can produce stronger storms than CIRs and are usually initiated by a southward interplanetary magnetic field (IMF), which enhances the night-side convection and increases the ring current. When CIRs and CMEs reach Earth, solar wind/magnetosphere coupling processes generate a rapid increase in Poynting flux; they result in an enhancement of Joule heating, which leads to disturbances in upper atmosphere composition, temperature, density, and winds (e.g., [4,[17][18][19][20]).…”
Section: Introductionmentioning
confidence: 99%
“…Low Earth Orbit (LEO) satellite is a valuable platform for Earth observation due to the low altitude, short period, and rapid connection with the ground [ 1 ]. The observation data collected by the LEO satellite have been widely used in geosciences with a wide area coverage, such as crustal deformation [ 2 , 3 ], ocean altimetry [ 4 ], Earth gravity field recovery [ 5 , 6 ], space weather [ 7 , 8 ] and remote sensing [ 9 , 10 ]. To ensure successful scientific applications undertaken by the LEO satellite, the precise orbit determination (POD) for the LEO satellite is essential.…”
Section: Introductionmentioning
confidence: 99%